Impact of COVID-19 pandemic on the mental health status among general masses: An in-deep analysis of the worst "hitters" of COVID-19 pandemic - Priyadarshni Rangarajan; Shaik F. Sultana; Kurian Punnoose; Hina Ahmed; Gautam Singh; V. Kiruthika; Suresh J. Babu; C. Swarnalatha; Abhishek Singh Nayyar (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: A plethora of studies have reported the adverse psychiatric outcomes among the general masses during the COVID-19 pandemic; however, not much data is available in relation to the Indian population from this perspective. The aim of the present study was to investigate the impact of the COVID-19 pandemic on the mental health status among the general masses in the Indian population. MATERIALS AND METHODS: The present study was planned in a cross-sectional study design between July 2020 and October 2021 in which a well-structured questionnaire, consisting of questions assessing the sociodemographic profile, while, also, specific questions related to the stress and anxiety-related variables, was used. The questionnaire was validated through intra-class correlation with a strong correlation of 0.84. The Chi-square test was used for statistical analysis to test the association between the studied variables, while P < 0.05 was considered statistically significant. RESULTS: On comparison between the male and female participants using stress and anxiety-related variables, 43.81% of males as against 56.19% of the female participants reported that they felt horrified due to the pandemic with the results being statistically highly significant (P = 0.0043). Similarly, 45.18% of male and 54.82% of female participants expressed apprehension due to the fear of the pandemic with the results being statistically significant (P = 0.0217). CONCLUSION: The research findings of the present study indicated that men and women responded to stress differently, with women experiencing greater sadness and anxiety and were found to be at a relatively greater risk for developing anxiety and depression than men.